Genetic Characterisation and Core Collection Construction of European Larch (Larix decidua Mill.) from Seed Orchards in Romania - Teodosiu, Maria; Mihai, Georgeta; Ciocîrlan, Elena; Curtu, Alexandru Lucian (MDPI AG, 2023)
European larch (Larix decidua L.) is an important forest tree species, with a large range and genetic variability; however, little is known about the characterisation of its genetic structure and diversity based on molecular markers in seed orchards, and no core collection—an improved tool for managing germplasm—has been developed for this species to date. In the present study, we employed nSSR molecular markers to characterise the genetic diversity and structure of five seed orchards and to construct a core collection for further use in breeding programmes. The results indicate that the values of heterozygosity in the seed orchards were slightly higher than the averages obtained in natural populations. The seed orchards displayed heterozygote deficiency, similar to other studies in Larix decidua or other Larix spp., which can be associated with a strong selective pressure on populations in a highly fragmented area. The presence of clones of autochthonous origin increased the allelic richness in the seed orchards where they were found. The degree of differentiation between individuals within the seed orchards was similar to that of populations originating from the Tyrolean Alps and Southern Carpathians (11.03% vs. 13% in the present study). The assignment, which was based on clustering, did not always match with the passport data (i.e., provenance), and we found that clones originating from stands from the northern Romanian Carpathians are distinct from the stands of the southern region, and most probably originated from a centre other than the Tyrolean Alps. The final extracted core collection (50 entries, 28% sampling effort) increases the rate of allele preservation, incorporates every allele from the entire collection, and provides candidate resources for the enhanced breeding of larch. The genetic characterisation of these germplasms will be essential for future breeding tasks, as well as for the preservation of valuable genotypes or populations.